БАСЛАЎЫШ КЛАССЛАРДА ОҚЫЎШЫЛАРДЫҢ СӨЙЛЕЎ ТИЛИН ӨСИРИЎДИҢ МЕТОД ҲӘМ УСЫЛЛАРЫ - Жумашева, Г.Х. (FAN va JAMIYAT, 2018)
The article is devoted to the problem of formation of communication skills of children in the Karakalpak language. In the article the author emphasizes the necessity of development of theoretical and methodical bases of teaching the second language on the basis of national ideology of independence, development of speech and thinking activities of children.